Juridical Analysis of the Implementation of Law Number 22 Year 2009 Concerning Road Traffic and Transportation in West Jakarta - Leonard Tasuno Laiya; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Modern society requires transportation in carrying out various activities. However, in reality, traffic accidents are a major source of death caused by various factors. This study aims to identify: 1). How is the implementation of Law no. 22 of 2009 concerning Road Traffic and Transportation; 2). What factors are the dominant aspects that trigger the formation of traffic accidents; 3). How are law enforcement efforts related to traffic disaster problems in the West Jakarta area. This research procedure is normative juridical which focuses on research objects of laws and regulations, with research on the problem of law enforcement efforts on traffic disaster problems in the West Jakarta area. Research result; 1). There are several articles in the implementation of Law no. 22 of 2009 which is a potential source of traffic violations 2). the dominant aspects that trigger the formation of traffic disasters in the West Jakarta area are; human negligence, lack of control over traffic signs, vehicles that exceed standard capacity, as well as cause and effect in nature; 3). Law enforcement against traffic violations is tried in an innovative way, namely on-site justice with the principle of implementing the Criminal Justice System.